2016
DOI: 10.1002/chem.201602162
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Fluorescence Turn‐On Sensor for Extracellular Calcium Ion Detection

Abstract: A highly water-soluble, fluorescence turn-on sensor for Ca(2+) is reported. The sensor affords high selectivity in sensing Ca(2+) over other biologically important metal cations. The dissociation constant of the sensor in binding Ca(2+) is 0.92 mm. Fluorescence microscopy experiments demonstrate that the sensor is cell-impermeable and capable of detecting extracellular Ca(2+) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…After that, 20 μL of the CellTiter 96 Aqueous One solution reagent (for MTS assay) was added into each well, followed by further incubation for 2 h at 37 °C. 17 , 31 , 36 The respective absorbance values were read on a Tecan Infinite M200 PRO plate reader spectrometer at 490 nm to determine the relative amount of formazan produced. Cell viabilities were calculated on the basis of the following equation (eq 3) where Abs s 490nm is the absorbance of the cells incubated with different concentrations of experimental probe solutions, Abs D 490nm is the absorbance of cell-free well containing only dye at the concentration that was studied, Abs c 490nm is the absorbance of cells only incubated in the medium, Abs D2 490nm is the absorbance of the cell-free well.…”
Section: Methodsmentioning
confidence: 99%
“…After that, 20 μL of the CellTiter 96 Aqueous One solution reagent (for MTS assay) was added into each well, followed by further incubation for 2 h at 37 °C. 17 , 31 , 36 The respective absorbance values were read on a Tecan Infinite M200 PRO plate reader spectrometer at 490 nm to determine the relative amount of formazan produced. Cell viabilities were calculated on the basis of the following equation (eq 3) where Abs s 490nm is the absorbance of the cells incubated with different concentrations of experimental probe solutions, Abs D 490nm is the absorbance of cell-free well containing only dye at the concentration that was studied, Abs c 490nm is the absorbance of cells only incubated in the medium, Abs D2 490nm is the absorbance of the cell-free well.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 8 shows some of the imine linkagebased COFs (13)(14)(15)(16)(17)(18) that have been realized by the condensation of amine and aldehyde building blocks. [49][50][51][52][53][54][55] The photoluminescence properties of these COFs have not been investigated, although some of these frameworks contain 1,3,5-TPB units.…”
Section: Discrete 135-tris(4 0 -Aminophenyl)benzenesmentioning
confidence: 99%
“…Another development in the area of chemo-sensing is the case of uorescence turn-on sensors. 17,18 Typically, uorescence turn-on sensors consist of uorophore and guest-receptor units, connected to each other by a covalent linkage. The pristine sensors exhibit very weak uorescence due to intramolecular PET ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium (Ca 2+ ) is one of the most abundant metals in the human body, making up to 2%wt of total human body weight, and plays a fundamental role in biological processes including secondary messengers critical for cell signalling, protein folding, and catalysis [ 1 , 2 , 3 , 4 ]. It has also been demonstrated that monitoring Ca 2+ concentrations is important within the environment.…”
Section: Introductionmentioning
confidence: 99%